PENGARUH CHAMBER PADA MESIN 3D PRINTING FDM TEHADAP HASIL PRODUK DENGAN MENGGUNAKAN FILAMEN ABS - zailani hamzah; Pristiansyah Pristiansyah; Dedy Ramdhani (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
3D printing technology using the Fused Deposition Modeling (FDM) system is one of the manufacturing processes currently being developed. The rapid prototyping process makes it easier for academics in research. Acrylonitrile Butadiene Styrene (ABS) filament material is the type of material used in this research. The purpose of this study was to determine the effect of the use of the chamber on the 3D printing machine DIY (Do It Yourself) FDM type Cartesian ender model on the quality of product dimensional accuracy results. The method used in this research is experimental by using a chamber on a 3D printing machine and using process parameters. The results of the research by testing and measuring, it is found that the chamber affects the accuracy of the product dimensions with the heat bed temperature (80 ℃), nozzle temperature (230 ℃), print speed (40 mm/s), infill density (40%) and the use of layer thickness. (0.20 mm) shows a significant result of product dimensional accuracy.